Atazanavir/ritonavir with lamivudine as maintenance therapy in virologically suppressed HIV-infected patients: 96 week outcomes of a randomized trial. (12th April 2018) - Fabbiani, Massimiliano; Gagliardini, Roberta; Ciccarelli, Nicoletta; Quiros Roldan, Eugenia; Latini, Alessandra; d'Ettorre, Gabriella; Antinori, Andrea; Castagna, Antonella; Orofino, Giancarlo; Francisci, Daniela; Chinello, Pierangelo; Madeddu, Giordano; et al.
Abstract: Objectives: To investigate the long-term safety and efficacy of a treatment switch to dual ART with atazanavir/ritonavir + lamivudine versus continuing a standard regimen with atazanavir/ritonavir + 2NRTI in virologically suppressed patients. Methods: ATLAS-M is a 96 week open-label, randomized, non-inferiority (margin −12%) trial enrolling HIV-infected adults on atazanavir/ritonavir + 2NRTI, with stable HIV-RNA <50 copies/mL and CD4 counts >200 cells/mm 3 . At baseline, patients were randomized 1:1 to switch to atazanavir/ritonavir + lamivudine or to continue the previous regimen. Here, we report the 96 week efficacy and safety data. The study was registered with ClinicalTrials.gov, number NCT01599364. Results: Overall, 266 subjects were enrolled (133 in each arm). At 96 weeks, in the ITT population, patients free of treatment failure totalled 103 (77.4%) with atazanavir/ritonavir + lamivudine and 87 (65.4%) with triple therapy (difference +12.0%, 95% CI +1.2/+22.8, P  =   0.030), demonstrating the superiority of dual therapy. Two (1.5%) and 9 (6.8%) virological failures occurred in the dual-therapy arm and the triple-therapy arm, respectively, without development of resistance to any study drug. Clinical adverse events occurred at similar rates in both arms. A higher frequency of grade 3–4 hyperbilirubinemia (66.9% versus 50.4%, P  =   0.006) and hypertriglyceridaemia (6.8% versus 1.5%, P  =   0.031) occurred with dual therapy, although this never led to treatment discontinuation. A significant improvement in renal function and lumbar spine bone mineral density occurred in the dual-therapy arm. The evolution of CD4, HIV-DNA levels and neurocognitive performance was similar in both arms. Conclusions: In this randomized study, a treatment switch to atazanavir/ritonavir + lamivudine was superior over the continuation of atazanavir/ritonavir + 2NRTI in virologically suppressed patients, with a sustained benefit in terms of improved renal function and bone mineral density.